A high-resolution characterization of the initiation of stress corrosion crack in Alloy 690 in simulated pressurized water reactor primary water. (February 2020) - Kuang, Wenjun; Was, Gary S.
Highlights: Microstructures of alloy 690 GBs at different SCC initiation stages were examined. Compact chromia film initially forms over RHAB due to rapid Cr diffusion. NiO and Cr2 O3 forms along the grain boundary when the surface oxide is breached. Crack forms along either the previous GB or the oxidized DIGM zone. Abstract: Stress corrosion crack initiation of alloy 690 in simulated pressurized water reactor primary water was studied through high-resolution characterization of grain boundaries at different stages of the initiation process. It was found that a compact layer of Cr2 O3 initially forms over a migrated grain boundary, driven by the diffusion of Cr. After the surface Cr2 O3 is breached by straining, oxygen diffusion results in formation of a mixture of NiO and Cr2 O3 along the grain boundary. The crack nucleates along either the previous grain boundary or the heavily oxidized migration zone when the boundary strength falls below the local stress.